Beautiful scenery of UMP in "Namaku Bedah" - Nor Fadzillah, Zulkipli (2017)
A picturesqeu scenery of UMP are the reason for Tanah Beris Film Sdn Bhd (TBFP) choosing UMP as the background for their latest drama ‘Namaku Bedah’. This 20 episode comedy genre drama will be aired starting 5th February 2017 in TV9 Kelakarama slot.